Mother-offspring vocal communication and temperament in cattle - Padilla de la Torre, Monica (2013)
Very little is known about cattle vocalizations. The few studies available in the literature have been conducted using animals under stress or very intensive husbandry conditions. Similarly, the individual consistency of behaviour in cattle has rarely been considered except in applied studies of constrained and isolated animals, and no previous research has attempted to address a possible association between vocal communication and temperament in cattle. The studies reported here address these gaps in our knowledge. I found that cattle contact calls have acoustic characteristics that give them individualized distinctiveness, in both adult cows and calves. These results were confirmed using playback experiments, where I found that there is bidirectional mother-offspring recognition, as has been recorded in other “weak hider” ungulates. Additionally, using visual and acoustic stimuli, I assessed individual cattle temperament. The results showed that there was no individual behavioural consistency in responses to a novel object presentations. However, calves behaved consistently more boldly than cows. Furthermore, there was significant individual consistency in responses to vocalisations of heterospecifics, when they were played back through a speaker in the field. Surprisingly, no correlations were found between the ability of cattle to identify their own mother/offspring and the acoustic features of their vocalisations, or behavioural responses in any other context. There were, however, significant correlations between one characteristic of vocalisations in adult cows (formant spacing) and the boldness of behavioural responses to both novel objects and auditory stimuli. Additionally, higher F0 in calf contact vocalizations correlated with boldness in the auditory stimuli experiment. These relationships imply that vocalisations may encode information about individual temperament, something which has rarely been documented. Surprisingly, no strong correlations were found between the behavioural responses to visual and acoustic stimuli, suggesting that individual consistency in behaviour across contexts was limited, and that behavioural plasticity could play an important role in determining responses in different environmental contexts. Overall, my results contribute to our knowledge of animal communication in mammals from a bioacoustic point of view, and they are also potentially relevant to studies of vocalizations as indicators of cattle welfare.